Attention of health teams to patients in critical condition (Research, Society and Development, 2022)
Critical patients are those who have pathologies that worsen their state of health, bringing the need for continuous and complex care to improve their condition. Thus, health teams are responsible for caring for these individuals. Study aims to identify the role of health teams in providing services to patients in critical condition. This is a literature review with a qualitative approach. The databases used for the search were Scielo and Lilacs using the health descriptors critical patients AND health staff. It took place in May and June 2022. Inclusion criteria were studies published in the last 5 years between 2018 and 2022, national and international, in Portuguese or in others, provided that translation into Portuguese was available. Exclusion criteria were: duplicate studies in the databases, not relevant to the present study and available only with payment. Theses, course conclusion works and abstracts were also excluded. Health teams are fully involved in the care of critically ill patients, and are responsible for ensuring that they offer all the means that contribute to their improvement. The role of these professionals is joint and must be discussed seeking to solve the needs found by each person in a critical state.